Efficacy and safety of maintenance and reliever combination budesonide–formoterol inhaler in patients with asthma at risk of severe exacerbations: a randomised controlled trial - Patel, Mitesh; Pilcher, Janine; Pritchard, Alison; Perrin, Kyle; Travers, Justin; Shaw, Dominick; Holt, Shaun; Harwood, Matire; Black, Peter; Weatherall, Mark; Beasley, Richard (Elsevier, 2013)
Background